Research on Benefit Analysis of CCHP-WSHP System in Vehicle to Building. Issue 1 (November 2020) - Zhao, Xin; Mu, Hailin; Li, Nan; Xue, Zhaoquan; Yang, Xiyue
Abstract: This paper proposes a combined cooling, heating and power (CCHP) system, which comprehensively uses water source heat pump (WSHP) system and vehicle to build (V2B) mode. The CCHP-WSHP-V2B could efficiently solve the problems when a CCHP or a WSHP operates independently. And it can acquire better system performance. In this mode, the CCHP system can flexibly exchange electricity with electric buses and coordinate electricity demand. The water source heat pump can supplement the cooling load and heating load of the system. Furthermore, a case study based on a hotel building is established and studied to verify the effectiveness of the model. The results of the case study show that the primary energy saving ratio, carbon dioxide emission reduction ratio, and annual total cost saving ratio comparing with the separate production system are 36.09%, 43.06%, and 25.47%, respectively.